Butenolide derivatives from Aspergillus terreus selectively inhibit butyrylcholinesterase - Cui, Xiang; Deng, Shanshan; Li, Guoyin; Zhang, Yunxia; Wang, Lining; Wu, Changjing; Deng, Yanru (Frontiers in Chemistry, 2022)
Two undescribed butenolide derivatives, asperteretal J (1) and K (2), together with thirteen known ones (3–15) were isolated from an endophytic fungus Aspergillus terreus SGP-1 which’s fermentation product exhibited selective inhibitory activity toward butyrylcholinesterase (BChE). The structures of new compounds were elucidated by HR-MS and NMR data, and the absolute configurations were determined by specific optical rotation comparison. All compounds were evaluated for cholinesterase inhibitory effects with galantamine as positive control. Compounds 4–8 selectively inhibited butyrylcholinesterase with IC50 values of 18.4–45.8 µM in competitive manners with Ki values of 12.3–38.2 µM. The structure-activity relationship was discussed. Molecular docking and dynamic simulation of inhibitor-enzyme complex were performed to better understand the interactions.